Escaping from Women's Marginalization in Hollywood Film Industry in T. J. Reid's "The Seven Husbands of Evelyn Hugo" - Jurianto, Izzah Putri; Saraswati, Rina; Datau, Rizal Octofianto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2023)
In the journey of the feminist movement, many efforts have been made to save marginalized women from patriarchy. Betty Friedan, an American feminist writer, reveals the controversial phenomenon of the concept of feminine mystique which restrains women from seeking their true selves due to oppression from various parties. In its practice, this phenomenon occurs in the Hollywood film industry, which is supposed to be an industry uncontaminated by gender discrimination. This study aims to investigate the issue of women's marginalization in Taylor Jenkins Reid’s The Seven Husbands of Evelyn Hugo by implementing Betty Friedan’s theory of feminine mystique. Valid data were collected through qualitative research methods by quoting narrations and dialogues from the characters in the novel. Furthermore, the data is processed and analyzed based on the theory used. This study presents the forms of Evelyn's marginalization in three areas: domestic, Hollywood film industry, and public and media. In the end, Evelyn Hugo's rejection of gender oppression in those three areas makes her able to escape from women’s marginalization and become a successful female icon in the Hollywood film industry.